Consumer interaction behavior, interaction expectation, trust and purchase intention : An empirical study on social media consumer / Hafiedah Afiqah Ishak - Ishak, Hafiedah Afiqah (2016)
Malaysia has been nominated as one of the highest internet users in the world. The use of social media create changes of the consumers way of thinking through emotions, needs, wants and demands that can influence the purchase intention. This research is to to explore a study on the relationship between social media interaction behavior, interaction expectation, and trust with purchase intention. The results of literature review analysis shows that 1) interaction expectation, 2) interaction behavior 3) trust and 4) purchase intention has relationship with each other. The target of this study is to working people and university student in Miri and Kota Samarahan, Sarawak- The result showed that all variables are reliable and have significant relationship with purchase intention.